Ir-6: A Novel Iridium (III) Organometallic Derivative for Inhibition of Human Platelet Activation. (2nd May 2018) - Shyu, Ren-Shi; Khamrang, Themmila; Sheu, Joen-Rong; Hsia, Chih-Wei; Velusamy, Marappan; Hsia, Chih-Hsuan; Chou, Duen-Suey; Chang, Chao-Chien
Abstract : Platelet activation has been reported to play a major role in arterial thrombosis, cancer metastasis, and progression. Recently, we developed a novel Ir(III)-based compound, [Ir(Cp ∗ )1-(2-pyridyl)-3-(4-dimethylaminophenyl)imidazo[1, 5-a]pyridine Cl]BF4 or Ir-6 and assessed its effectiveness as an antiplatelet drug. Ir-6 exhibited higher potency against human platelet aggregation stimulated by collagen. Ir-6 also inhibited ATP-release, intracellular Ca 2+ mobilization, P-selectin expression, and the phosphorylation of phospholipase C γ 2 (PLC γ 2), protein kinase C (PKC), v-Akt murine thymoma viral oncogene (Akt)/protein kinase B, and mitogen-activated protein kinases (MAPKs), in collagen-activated platelets. Neither the adenylate cyclase inhibitor SQ22536 nor the guanylate cyclase inhibitor 1H-[1, 2, 4]oxadiazolo[4, 3-a]quinoxalin-1-one significantly reversed the Ir-6-mediated inhibition of collagen-induced platelet aggregation. Moreover, Ir-6 did not considerably diminish OH radical signals in collagen-activated platelets or Fenton reaction solution. At 2 mg/kg, Ir-6 markedly prolonged the bleeding time in experimental mice. In conclusion, Ir-6 plays a crucial role by inhibiting platelet activation through the inhibition of signaling pathways, such as the PLC γ 2–PKC cascade and the subsequent suppression of Akt and MAPK activation, thereby ultimately inhibiting platelet aggregation. Therefore, Ir-6 is a potential therapeutic agent for preventing or treating thromboembolic disorders or disrupting the interplay between platelets and tumor cells, which contributes to tumor cell growth and progression.